Shorter Survival in Familial versus Idiopathic Pulmonary Arterial Hypertension is Associated with Hemodynamic Markers of Impaired Right Ventricular Function. (1st September 2013) - Brittain, Evan L.; Pugh, Meredith E.; Wheeler, Lisa A.; Robbins, Ivan M.; Loyd, James E.; Newman, John H.; Larkin, Emma K.; Austin, Eric D.; Hemnes, Anna R.
Abstract : Although individuals with familial pulmonary arterial hypertension (FPAH) have more severe hemodynamics, compared to individuals with idiopathic PAH (IPAH), it is unclear whether this translates into a survival difference. The influence of right ventricular (RV) function on survival in these groups is also unknown. We reviewed hemodynamic data and health information from a prospective institutional database of 57 FPAH and 66 IPAH patients registered with the Vanderbilt Pulmonary Hypertension Research Cohort. We compared hemodynamics at the time of diagnosis between the two groups and calculated pulmonary arteriolar capacitance (PC) and RV stroke work index (RVSWI). Using survival analysis, we compared freedom from a 5‐year composite of death or lung transplantation in FPAH and IPAH patients. The composite outcome of death or transplant at 5 years from diagnosis was significantly increased in FPAH (log rank P < 0.001). PC and RVSWI were significantly decreased in FPAH, compared to IPAH ( P < 0.001 for both). In univariate analysis, PC (odds ratio [OR]: 0.17 [95% confidence interval (95% CI): 0.03–0.83]) and RVSWI (OR: 0.86 [95% CI: 0.77–0.95]) were predictors of mortality, as were cardiac index (OR: 0.17 [95% CI: 0.06–0.51]) and PVR (OR: 1.1 [95% CI: 1.01–1.12]). Among FPAH patients, RVSWI was lower in those who died or received a transplant than in survivors ( P = 0.006), while PC was not ( P = 0.5). We found significantly worse event‐free survival and significantly lower PC and RVSWI in FPAH than in IPAH. In FPAH patients who died or underwent transplantation, RVSWI was lower than that in survivors, suggesting disproportionate RV dysfunction.